A case series of four cases of atypical ectopic pregnancies - Pravin Kumar Thakare; Rupali Sitaram Patil; Narendra Bachewar (International Journal of Health and Clinical Research, 2021)
Background: Atypical ectopic pregnancies need high level of suspicion. Early diagnosis and timely intervention can save future complications. Ruptured ectopic pregnancy is a nightmare sometimes, however high index of suspicious can help to diagnose and manage patients uneventfully. Objective: The incidence of atypical ectopic pregnancy seems to have increased. We are presenting our experience of such rare presentations of atypical ectopic pregnancy successfully managed at our tertiary care center.Case report: a 24-year-old woman at the gestation stage of 8 weeks presented with pain in the lower abdomen and slight per vaginal bleeding. On detailed investigations and laparatomy was found to have primary abdominal pregnancy. A 23-year-woman, with complaints of pain in abdomen and nausea, vomiting at estimated gestational age of 8 weeks was found to have interstitial pregnancy. A 30 yr P2L2 with history of dilatation and evacuation twice for early pregnancy complaining of pain in abdomen since 2 months was having chronic interstitial pregnancy. And a 32yr P2L2 presented with pain in abdomen with HCG 50000 and USG report of right (rudimentary horn) ruptured ectopic pregnancy was managed successfully.Conclusion: Atypical ectopic pregnancies need high level of suspicion. Early diagnosis and timely intervention can save future complications.